Domestication or Foreignization: The Translation Orientation of Blender Parts Terms in English-Indonesian User Manual - Mukminin, Muhamad Saiful; Muhhit, Ahmad Abdul (STKIP PGRI Ponorogo Press, 2025)
The purpose of this study is to identify and analyze the translation orientation of blender part terms, whether it leans toward a domestication strategy, foreignization, or a combination of both. This research is a descriptive qualitative study using a translation text analysis approach. The data were obtained from bilingual (English–Indonesian) user manuals of Philips blenders, model types HR2010 and HR2223, which contain lists and descriptions of blender components. The data collection technique involved documentation by transcribing source language terms (English) and their equivalents in the target language (Indonesian). The terms were then classified based on the translation strategy used. The data analysis techniques included data reduction, data presentation, and conclusion drawing, referring to Venuti’s theories of domestication and foreignization. The results show three translation orientation patterns: domestication (replacement of foreign terms, phrase structure adapted to the target language, simplification of information), foreignization (retaining widely recognized foreign terms), and a combination of both (retaining foreign terms while structuring phrases according to the target language). In conclusion, the translation of blender terminology is adaptive, prioritizing readability for local users without compromising the accuracy of technical terms, and the combined approach proves effective in the context of technical translation for household appliance instructions.